Buckling analysis of a bi-directional strain-gradient Euler–Bernoulli nano-beams - Çelik, Murat; Artan, Reha (International Journal of Structural Stability and Dynamics, 2020)
Investigated herein is the buckling of Euler–Bernoulli nano-beams made of bi-directional functionally graded material with the method of initial values in the frame of gradient elasticity. Since the transport matrix cannot be calculated analytically, the problem was examined with the help of an approximate transport matrix (matricant). This method can be easily applied with buckling analysis of arbitrary two-directional functionally graded Euler–Bernoulli nano-beams based on gradient elasticity theory. Basic equations and boundary conditions are derived by using the principle of minimum potential energy. The diagrams and tables of the solutions for different end conditions and various values of the parameters are given and the results are discussed.
CRIS-Team Scopus Importer:2020-10-23
Keywords: Bi-directional functionally graded materials; Buckling; Euler–Bernoulli nanobeams; Method of initial values; Stability of beams; Theory of gradient elasticity; Transfer matrix